Implementation of Data Mining Using C4.5 Algorithm on Customer Satisfaction in Tirta Lihou PDAM - Titin Handayani Sinaga; Anjar Wanto; Indra Gunawan; Sumarno Sumarno; Zulaini Masruro Nasution (Information Technology and Science (ITScience), 2021)
This application applies the C4.5 Algorithm to decide customer satisfaction, the C4.5 algorithm is one of the algorithms used to classify or segment, or group and it is predictive. This type of research is a classification with the concept of data mining involving 150 customers of PDAM Tirta Lihou in Totap Majawa Kab. Simalungun can be categorized as: